2020
DOI: 10.1371/journal.pone.0236199
|View full text |Cite|
|
Sign up to set email alerts
|

Ultraviolet A light effectively reduces bacteria and viruses including coronavirus

Abstract: Antimicrobial-resistant and novel pathogens continue to emerge, outpacing efforts to contain and treat them. Therefore, there is a crucial need for safe and effective therapies. Ultraviolet-A (UVA) phototherapy is FDA-approved for several dermatological diseases but not for internal applications. We investigated UVA effects on human cells in vitro, mouse colonic tissue in vivo, and UVA efficacy against bacteria, yeast, coxsackievirus group B and coronavirus-229E. Several pathogens and virally transfected human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 39 publications
6
74
0
Order By: Relevance
“…This assumption is consistent with the work by Darnell et al . [ 527 ] who demonstrated that UV-A radiation does not damage SARS-CoV-1 (a virus similar to SARS-CoV-2), but contradicts more recent work [ 511 ], suggesting that UV-A does contribute to the inactivation of SARS-CoV-2. It has also been shown that the viruses can be damaged by peroxides and other reactive oxygen species, which are created by UV-A radiation [ 528 ].…”
Section: Linkages Between Covid-19 Solar Uv Radiation and The Montrmentioning
confidence: 94%
See 1 more Smart Citation
“…This assumption is consistent with the work by Darnell et al . [ 527 ] who demonstrated that UV-A radiation does not damage SARS-CoV-1 (a virus similar to SARS-CoV-2), but contradicts more recent work [ 511 ], suggesting that UV-A does contribute to the inactivation of SARS-CoV-2. It has also been shown that the viruses can be damaged by peroxides and other reactive oxygen species, which are created by UV-A radiation [ 528 ].…”
Section: Linkages Between Covid-19 Solar Uv Radiation and The Montrmentioning
confidence: 94%
“…As we show below, these long lifetimes of SARS-CoV-2 particles decrease greatly upon exposure to UV-C and UV-B radiation. Also some deactivation by UV-A radiation currently cannot be ruled out [ 511 ]. Research on lifetimes focuses on indoor surfaces and mainly in health-care facilities [ 512 514 ] where no solar UV-B radiation is present and rigorous biocidal disinfection routines are followed.…”
Section: Linkages Between Covid-19 Solar Uv Radiation and The Montrmentioning
confidence: 99%
“…specific intensity, peak wavelength, exposure time and distance to target tissue), reduces bacteria, fungi, and viruses including coronavirus-229E but does not harm human ( in vitro) or murine ( in vivo) columnar epithelial cells. [6] Moreover, UVA exposure of coronavirus-229E transfected human primary tracheal cells led to activation of the MAVS protein, reduction in spike protein, and resumption of cell proliferation similar to uninfected cells, suggesting that UVA may induce a beneficial antiviral state in infected human cells. [6]…”
Section: Introductionmentioning
confidence: 99%
“…Reference [10] indicates that with a dose close to 3800 mJ/cm 2 of UVA is possible to achieve a reduction of 90% of Sars-CoV-2. Reference [11] analyzes other microorganisms, showing for example that a dose of 3600 mJ/cm 2 in the UVA range is needed for inactivating Escherichia Coli. Besides the work of R. Tomb et.al.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning other microorganisms Rezaie et.al. [11] analyses the response to UVA. As an example, they show that for inactivating Escherichia Coli a dose of 3600 mJ/cm 2 is needed.…”
Section: Introductionmentioning
confidence: 99%